A first for forensic genetics in Africa: successful identification of skeletal remains from the marine environment using massively parallel sequencing. (November 2020) - Finaughty, Chandra; Reid, Kate Megan; Alli, Iekram Hoosen; Heathfield, Laura Jane
Highlights: Two males went missing at sea in unrelated events and times. Two partial sets of decomposed human remains washed up from the sea. These were successfully determined to be from the same origin using MPS. DNA tests indicated male, in contrast to external features and pelvis assessment. We report the first successful use of MPS on lysates from a marine decomposition case. Abstract: In unrelated circumstances, two young adult males allegedly went missing off the coast of Cape Town, South Africa, within two months of each other. Weeks after the second disappearance, a decomposed human lower limb was recovered from a beach in Cape Town, followed by a washed-up decomposed hand three days later. An item of female clothing was found with the remains, and preliminary analysis of the skeleton indicated a female, leading to confusion regarding the possible identity of the decedent. Consequently, DNA analyses were requested to determine the biological sex of the remains, and whether the two sets of remains originated from the same individual. Various samples were collected, including bone, nails and swabs of soft tissue. DNA quantity and quality varied between sample types, with better results obtained from metacarpal bone and swab lysates. DNA profiling revealed a male sex, which suggests cognitive bias may have played a role in initial sex estimations. In addition, massively parallel sequencing confidently matched the two sets of remains (random match probability: 1 in 2.70 x 10 31 ). These results were a first for Africa where massively parallel sequencing was successfully used and assisted in the identification of human remains, thus, affording closure to the next-of-kin. Moreover, this constitutes the first global report where soft tissue lysates from a marine decomposition case yielded full DNA profiles with a massively parallel sequencing approach.